Fluoride exposure and CALCA methylation is associated with the bone mineral density of Chinese women. (August 2020) - Sun, Renjie; Zhou, Guoyu; Liu, Lihua; Ren, Lijun; Xi, Yu; Zhu, Jingyuan; Huang, Hui; Li, Zhiyuan; Li, Yan; Cheng, Xuemin; Ba, Yue
Abstract: Excessive exposure to fluoride has been reported to affect bone mineral density (BMD). CALCA expression plays a critical part in bone formation. However, the role of CALCA in the association between fluoride and BMD is not known. We conducted a cross-sectional study and recruited 722 women in rural areas of Henan Province, China, to assess the relationship between fluoride exposure, CALCA methylation, and BMD. Urinary levels of fluoride, CALCA methylation, and BMD were measured by a fluoride ion-selective electrode, standalone ultrasound bone densitometer, and quantitative methylation-specific polymerases chain reaction, respectively. The association among fluoride exposure, CALCA methylation, and BMD was age-specific. Specifically, BMD was negatively correlated with methylation ( β : −0.008; 95% CI : −0.016, 0.000) and fluoride exposure ( β : −0.063; 95% CI : −0.129, −0.002) in women over 45 years and 50–54 years of age, respectively, whereas methylation was positively correlated with fluoride exposure ( β : 4.953; 95% CI : 1.162, 8.743) in women aged 40–44 years. Besides, increased BMD in women aged 45–49 years induced by the interactive effect of the highest methylation of CALCA exon 1 (tertile 3) and fluoride exposure was observed ( P for interaction < 0.05). Our findings suggest an age-specific association between exposure to excessive fluoride, CALCA methylation, and BMD in a rural population of women in China. Notably, the susceptibility of BMD to fluoride exposure may be modified by CALCA methylation. Graphical abstract: Image 1 Highlights: Excessive fluoride exposure is positively related to CALCA methylation in women. CALCA methylation in Chinese women is negatively associated with BMD. Long-term excessive fluoride exposure is negatively related to BMD in women. BMD in women with CALCA hypermethylated is more susceptible to fluoride. The statistical associations are age-specific and mainly observed in older women.